River-Space Development as a Social Interaction Space through the Placemaking Approach - Laras Miradyanti; Felia Srinaga; Julia Dewi (Built Environment Studies, 2021)
Urban water management has increasingly given the use of rivers to infrastructure, industry, and navigation; stripping away its use as a space and cutting people off while creating the phenomenon of social disconnection. Awareness to implement social planning during river development is important in order to integrate rivers into the urban fabric. This research examines the ‘City is Not a Tree’ theory as a basis to understand how cities need to have a semi-lattice structure with overlapping spaces in order to integrate themselves into the city. As the nature of this research is bottom-up, it saw appropriate the placemaking approach in creating river-spaces into a place for the people. Method used in this research includes analysis and comparison to theories, guides and ideal precedents. Furthermore, this research resulted in finding guides for creating good river-spaces through the placemaking approach. The guides are of elements and variables needed to create a good river-space and a guide for the required programs that need to be implemented. Through this research, it is found that developing river-spaces as a space to host social interaction with the placemaking approach, not only creates a livelier environment but also improves the overall quality of the river-space